Musculoskeletal Disorders Risk Levels in Tofu Workers in North Aceh: An Ergonomic Assessment - Cut Ita Erliana; Iskandar Hasanuddin; Yuwaldi Away; Raja Ariffin Raja Ghazilla (Yayasan Riset dan Pengembangan Intelektual (YRPI), 2023)
Tofu is a soy-based food that is popular in Indonesia. One of the supporting factors is that it has high nutritional value and low price. Tofu is produced by micro, small, and medium enterprises (MSMEs) in all provinces in Indonesia, including in the region of Aceh. Based on the results of observations, the tofu production process still predominantly uses human labor, starting from the washing process to the cutting process. This activity is carried out every day with a high repetition rate. If this is allowed to happen for a long time, workers will be exposed to the risk of musculoskeletal disorders. This study uses the Cornell Musculoskeletal Disorders (CMDQ) questionnaire to assess the workers' work posture and determine the level of occupational hazard risk using the Rapid Entire Body Assessment (REBA) method. The results of the distribution of questionnaires show that the body parts that experienced pain complaints were the shoulder (right dan left), upper back, upper arm (right and left), lower back, forearm (right and left), also wrist (right and left). It happens in the filtering process. The results of the assessment of work posture with the REBA method show the score of work posture in the filtering process is 13, which means that the filtering posture of workers has a very high risk and must be improved immediately. The present research recommended additional intervention that includes engineering and administrative control methods for reducing those workers' complaints of muscle pain.